2014
DOI: 10.1038/jcbfm.2014.138
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Normal Pressure Hydrocephalus: Cerebral Perfusion Measured with pCASL before and Repeatedly after CSF Removal

Abstract: Pseudo-continuous arterial spin labeling (pCASL) measurements were performed in 20 patients with idiopathic normal pressure hydrocephalus (iNPH) to investigate whether cerebral blood flow (CBF) increases during the first 24 hours after a cerebrospinal fluid tap test (CSF TT). Five pCASL magnetic resonance imaging (MRI) scans were performed. Two scans were performed before removal of 40 mL CSF, and the other three at 30 minutes, 4 hours, and 24 hours, respectively after the CSF TT. Thirteen different regions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 40 publications
3
27
0
Order By: Relevance
“…The inclusion process and demographics have been described in detail elsewhere. 11 One patient classified as having unlikely iNPH did not fit into the MR imaging head coil and was excluded. Because of technical problems, quantitative MR imaging was not acquired in 2 patients, who were excluded.…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inclusion process and demographics have been described in detail elsewhere. 11 One patient classified as having unlikely iNPH did not fit into the MR imaging head coil and was excluded. Because of technical problems, quantitative MR imaging was not acquired in 2 patients, who were excluded.…”
Section: Patientsmentioning
confidence: 99%
“…We reported in a previous study of patients with iNPH, by using a manual approach that is available in the same software, that the volume of the lateral ventricles decreases at 30 minutes and 4 hours following a lumbar puncture with removal of 40 mL of CSF (Fig 1B). 11 The drawback with the manual method is that it requires detailed anatomic knowledge and is rather time-consuming.…”
mentioning
confidence: 99%
“…Some limitations need to be considered. We previously reported that the repeatability of ASL perfusion in iNPH patients is acceptable if the scans are performed with an interval of 30 minutes 11 . It is not known how high the physiological variability is in iNPH patients if the interval between scans is several months.…”
Section: Discussionmentioning
confidence: 99%
“…The same investigations of clinical symptoms and a second MRI were performed at a follow‐up visit 3 months after shunt surgery. The patient cohort has been described in detail in previous studies 3,11,12 . The study was approved by the local ethics committee in Uppsala, Sweden, and written informed consent was obtained from all patients.…”
Section: Methodsmentioning
confidence: 99%
“…Within these studies, correlations of clinical improvement and increased cerebral blood flow (CBF) have been examined. A recent study by Virhammer et al found an improvement in gait and balance dysfunction among NPH individuals after CSF tap testing due to increased CBF in the frontal and lateral lobes (Virhammar, Laurell, Ahlgren, Cesarini, & Larsson, 2014). Another study using [15O]H 2 O uptake found that patients with clinical improvement post shunt treatment showed increased uptake within the frontal cortex (P.…”
Section: Pathophysiologymentioning
confidence: 99%